FACTORS INFLUENCING TEACHERS’ BEHAVIORAL INTENTION TO USE THE SMART BOARD - LOH , WAI LING (2018)
The benefits of Smart board (SB) usage are well researched, documented and published. Existing evidence has proven that teachers’ acceptance is vital for SB technology to be adopted and implemented successfully. Nonetheless, studies in investigating SB technology acceptance in the Malaysian education sector are presently very limited